Identification of Seagrass Ecosystem in the Waters of the Makasar Island, Baubau City - Junaidin Sirza, La Ode Muhammad; Cahyani, Waode Sitti; Bugis, Nila Nikmatia; Hasanah, Nur (AgriSains, 2020)
The seagrass ecosystem is one of the important ecosystems in coastal areas and has high productivity. The existence of seaggrass has an important for other marine biota, human, and the environment so that the possibility of a decrease in quality and quantity can reduce the benefits generated by seagrass beds and make an significant impact for the surrounding environment. This study aims to identify the types of seagrass and the percentage of seagrass cover in the waters of Makasar Island, Baubau City. This research was conducted on February 2020 in Makasar Island Waters, Baubau City, South East Sulawesi. The observation of the condition of seagrass cover and the density of the seagrass was carried out using a quadratic transect of 0.5 m x 0.5 m with a line transect length of 100 m. The results of this study indicate the types of seagrass found in Makasar Island waters, namely Enhallus accoroides, Cymodocea serullata, Halophila ovalis and Thalassia hemprichii with a wide range of seagrass cover is 7.39 - 51.7%. The area of seagrass cover in Makasar Island is categorized as bad and damaged. The water physic and chemical parameters are still optimum in supporting the development of seagrass.